Perception of the glass ceiling and job satisfaction among women in the agricultural industry of Latin America - Maria Lopez-Escober; Sarahi Morales; Luis Sandoval; Raul Soto (Journal of International Agricultural and Extension Education, 2024)
The representation of women in the agricultural sector of Latin America remains disproportionate in comparison to their male counterparts. However, women represent an untapped potential for economic growth in the region. The purpose of this study was to evaluate job satisfaction and to measure beliefs about the glass ceiling among women in the Latin American agricultural industry. Given the regional scope of this study, a descriptive-exploratory methodology was used through the administration of an online survey instrument (Gall et al., 2007). Participants were alumni from the Zamorano Pan-American Agricultural School who are working in the Latin American agricultural industry. They were asked to complete an online survey instrument via Qualtrics. The instrument included three sections: (1) the Job Satisfaction Scale (JSS) developed by Spector (1985), (2) the Career Pathway Survey (CPS) developed by Smith et al. (2012), and (3) a demographics section. Descriptive statistics and a K-means partitional clustering algorithm were used to assess the research objectives. The findings of this study indicate that it is plausible that women in the Latin American agricultural industry pursue leadership positions at some point in their professional lives. However, when they fail to attain them, they decide to accept the existing barriers and cease attempting to overcome them. The study found no significant correlation between job satisfaction and beliefs about the glass ceiling. Moreover, the prevailing beliefs of women alumni of Zamorano working in the Latin American agricultural industry were acceptance and resignation. This suggests that the potential of women in the industry may not be fully reached in the near future unless significant changes occur within the workplace of the agricultural industry in the region.
Keywords: women leadership; glass ceiling; Latin America; barriers; job satisfaction